Tafʿīl Dawr al-Ansyiṭah al-Madrasiyyah li-Tanmiyat al-Mahārāt al-Lughawiyyah (Maʿhad Dārussalām Gontor li al-Tarbiyah al-Islāmiyyah al-Ḥadīthah Namūdhajan) - Abdul Hafidz Zaid (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2017)
In recent decades, the Arabic language has gained increasing global prominence due to the rapid growth of the Muslim population and the expanding interest in learning Arabic among non-native speakers, both in Arab countries and in educational institutions worldwide. This growing demand has encouraged scholars and language educators to explore effective strategies that facilitate the acquisition of Arabic as a foreign language. Among these strategies, the establishment of a comprehensive linguistic environment is widely recognized as one of the most influential factors in promoting successful language learning. Pondok Modern Darussalam Gontor (Islamic Boarding School of Darussalam Gontor) has long recognized the importance of creating such an environment. Since adopting the Direct Method as the foundation of its Arabic language instruction, the institution has consistently cultivated an atmosphere that encourages students to communicate in Arabic in their daily lives. To reinforce language acquisition, Gontor integrates numerous extracurricular activities, including speech contests, theatrical performances, debates, language games, and other Arabic-based competitions. In addition, a dedicated student language committee is responsible for organizing and supervising language-related programs throughout the boarding school. Rather than relying primarily on modern instructional technologies, Gontor has developed a distinctive educational approach centered on continuous exposure to Arabic through an immersive linguistic environment. This environment enables students to practice the language naturally and consistently, thereby strengthening their communicative competence and facilitating the acquisition of Arabic as a foreign language.